2021
DOI: 10.3102/01623737211013782
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Developmental Education: The Causal Effect of Mobile App Courseware on the College Outcomes of Developmental Education Students

Abstract: Developmental education, in which college students deemed unprepared for college-level coursework enroll in non-credit-bearing courses, is widespread in American higher education. This study evaluates the effect of mobile app courseware on the college outcomes of developmental education students. We used a research design that randomly assigned course sections to receive access to the apps or not. The results show that access to the apps significantly improved student performance in developmental education out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The main result of the study by Hoareau et al [10] was that the social context of the school was an important factor to be considered when studying teachers' beliefs and acceptance of technology. Giani et al [11] analyzed the influence of mobile applications on university achievement of developmental education students. Results showed that using APP significantly improved students' performance in developing educational outcomes and slightly improved mid-college adherence and performance, but did not affect academic attainment over study time frame.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The main result of the study by Hoareau et al [10] was that the social context of the school was an important factor to be considered when studying teachers' beliefs and acceptance of technology. Giani et al [11] analyzed the influence of mobile applications on university achievement of developmental education students. Results showed that using APP significantly improved students' performance in developing educational outcomes and slightly improved mid-college adherence and performance, but did not affect academic attainment over study time frame.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Despite limited exposure, pre-service teachers strive to meet field study requirements through their dedicated efforts. The pandemic-induced switch to distance learning, including blended approaches, has impacted students' preparedness due to sudden environmental changes and curriculum reforms (Giani & Martin, 2021).…”
Section: Theme 6: Working Stationmentioning
confidence: 99%
“…Therefore, the transformations in learning environments because of the new normal causes stress to pre-service teachers, to which 'they felt more challenged like an excessive burden waited on them' (Al Abiky, 2021), partly because of the absence of their readiness for the situation. One of the most widespread reasons for students' lack of readiness in their endeavours is the abrupt transformation of the learning environment, as well as the curriculum and pedagogical changes that have recently been implemented (Giani & Martin, 2021). In light of the pandemic, they have felt unprepared; however, they need to adopt with the emerging educational technologies for them to maximize their potentials (Laguitao, Cubalit, Teppang, Cruz, & Bautista, 2021).…”
Section: Introductionmentioning
confidence: 99%